The Influence of Learning Facilities and Practical Activities on Student Competence in the Diploma III Culinary Arts Study Program at the Palembang Tourism Polytechnic - Khadijah Khadijah; Fatma Az Zahra; Muhammad Halfi Indra Syahputra; Hanif Hasan (Brilliant International Journal Of Management And Tourism, 2026)
Student competency is a key learning outcome in vocational education, particularly in study programs that emphasize the mastery of practical skills such as culinary arts. This study aims to analyze the influence of learning facilities and practical activities on the competency of students in the Diploma III Culinary Arts Study Program at the Palembang Tourism Polytechnic. The study used a quantitative approach with an associative design through a survey method. Data were collected using a closed questionnaire from 59 students, measuring learning facilities (study room facilities and practice facilities), practice activities, and student competency understood as perceived competence ( self-perceived competence ). The analysis was conducted through descriptive statistics, Cronbach's Alpha reliability tests, and multiple linear regression at a significance level of 5%. The results showed that students rated practice facilities very positively, while study room facilities still left ratings ranging from "fair" to "poor". The regression test indicated that learning facilities and practical activities had a positive and significant effect on student competency, with a moderate contribution to the model's explanation. This finding confirms that the support of learning facilities and the implementation of structured practice complement each other in shaping the competency of vocational students. However, improving the comfort and completeness of study room facilities is still needed for competency formation to take place more optimally.